Soil fertility effects governing growth and nodule parameters at anthesis of two winged bean cultivars with a typic eutrustox - Purcino, H. M.A.; Purcino, A. A.C.; Lynd, J. Q. (Pesquisa Agropecuaria Brasileira, 2014)
Winged Bean cultivars, Tinge WB-21-8 and Siempre WB-12-11, were grown with complete factorial soil fertility experiments for P, K, Ca, Mg, and S combinations on a Typic Eutrustox (dark-red latosol) from Central Brazil. Nitrogenase (C2H2 reduction), growth, and associated nodule enzyme parameters and corn position were determined at anthesis. Highly significant increases in nitrogenase activity levels resulted with applied P and K for both cultivars with significant increases for Ca additions. Growth, nodulation and cytosol enzyme activity levels of GOT, GDH, GS and GOGAT all increased significantly with applied P, with the exception of GDH to applied K. a KG was increased to highly significant levels with K treatment. Cytosol composition was increased significantly for each plant nutrient element contained in the treatment combinations. Highly significant in verse retroversion existed for K and Na. Na was negatively correlated with every parameter determined in these studies for both cultivars. Practical application of these data include the requirement for adequate available, soil K and P for increased symbiotic N fixation and NH4+ incorporation into amino acid components of the host legume symbiont.